The Educational Mission of the Peruana Union University Head- quarters located in Tarapoto and Perception in Selected Public - Turpo, Josué (2011)
This research seeks to understand the perception of whether the Peruana Union University meets or not, with what it says in his declaration of mission through a SWOT (Strengths, Weaknesses, Opportunities and Threats). A sample of 121 people distributed among university students, teachers, developer, administra- tion, and ex-student was made. Also, a questionnaire was administered to obtain information about SWOT (Strengths, weaknesses, opportunities and threats) of the Peruana Union University in relation to their declaration in their Mission. The results of these tests were analyzed through statistical analysis package SPSS for educational research (15.0), by frequency analysis. The results found that the Pe- ruana Union University shows a positive perception in relation to fulfill its mission regarding to the studied population. The analysis showed that student’s environ- ment was as their main fortress with 61.2% showing that it is one of the main areas of UPeU, Tarapoto.